Inflammatory PDLSCs promotes T cell migration and activation: A pilot study - REN Le; WEI Yu; MA Pengfei; YI Zimei; ZHAO Jiechen; WU Junhua (Kouqiang hemian waike zazhi)
[Objective:] To explore the inflammatory periodontal ligament stem cells (PDLSCs) on T cell immunity in periodontitis conditions and its possible mechanism. [Methods:] PDLSCs were stimulated with phosphate buffered saline （PBS) and lipopolysaccharide (LPS) to mimic PDLSCs in healthy and inflammatory environments, and then the two groups of conditioned medium (CM) were collected, namely healthy PDLSCs CM (CON‐CM group) and inflammatory PDLSCs CM (LPS‐CM group). The same batch of culture medium was collected as the negative control (NC group) as well. They were used to act on human normal T lymphocyte line H9 cells respectively to observe the effects of different CM on T cell proliferation and migration. Furthermore, phytohemagglutinin‐L (PHA‐L) was used to stimulate T cell immune activation, and CM was used to treat H9 cells in the activated state, then the expression of T cell immune activation related genes—interleukin‐2 (IL‐2), interferon‐γ (IFN‐γ), interleukin‐17 (IL‐17) and CC chemokine receptor 6 (CCR6) were detected, and the effect of LPS stimulation on the secretion of CC chemokine ligand 20 (CCL20) by PDLSCs was observed. [Results:] Compared with the NC group and the CON‐CM group, the LPS‐CM group could promote the proliferation and migration of T cells, as well as the expression of IL‐2, IFN‐γ, IL‐17 and CCR6 mRNA (P<0.05). While the content of CCL20 secreted by PDLSCs was significantly increased under LPS stimulation (P<0.001). [Conclusion:] This study provides evidence that normal PDLSCs have certain immunomodulatory effects, while inflammatory PDLSCs may promote T cell proliferation, migration, activation and other immunobiological behaviors through the CCL20‐CCR6 axis.